1990
DOI: 10.1021/bc00001a006
|View full text |Cite
|
Sign up to set email alerts
|

Sulfhydryl site-specific crosslinking and labeling of monoclonal antibodies by a fluorescent equilibrium transfer alkylation crosslink reagent

Abstract: The site-specific intramolecular cross-linking of sulfhydryls of monoclonal antibodies via a new class of "equilibrium transfer alkylation cross-link (ETAC) reagents" is described. Following complete or partial reduction of interchain disulfides with dithiothreitol (DTT), two murine IgG2a monoclonal antibodies, 225.28S and 5G6.4, were reacted with alpha,alpha-bis[(p-tolylsulfonyl)methyl]-m-aminoacetophenone (ETAC 1a) and a fluorescent conjugated derivative, sulforhodamine B m-(alpha,alpha-bis(p-tolysulfonylmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Arano et al (1994) reported mercaptoethanol reduction of the disulfide bonds of a monoclonal antibody against osteogenic sarcoma to generate 6 to 7 thiols per molecule. Using a procedure similar to that described herein, del Rosario et al (1990) reported the use of DTT at 37°C for approximately 5 h to cleave the hinge region disulfides of antibodies. Upon radioiodination, one of the half antibody preparations possessed immunoreactivity in the highest range typically obtained for routine radioiodination of this antibody.…”
Section: Disc Ussl O Nmentioning
confidence: 99%
“…Arano et al (1994) reported mercaptoethanol reduction of the disulfide bonds of a monoclonal antibody against osteogenic sarcoma to generate 6 to 7 thiols per molecule. Using a procedure similar to that described herein, del Rosario et al (1990) reported the use of DTT at 37°C for approximately 5 h to cleave the hinge region disulfides of antibodies. Upon radioiodination, one of the half antibody preparations possessed immunoreactivity in the highest range typically obtained for routine radioiodination of this antibody.…”
Section: Disc Ussl O Nmentioning
confidence: 99%
“…Although bis-alkylating agents have been widely used for peptide cyclization and labelling, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] only a few examples of bis-alkylation of a previously reduced pair of Cys residues of an antibody using a bis-sulfone linker and bromomaleimides have been described in the literature. [39][40][41][42][43] Thus new chemical entities able to preserve the native structure of the antibodies after bioconjugation are needed.…”
Section: â–Ș Introductionmentioning
confidence: 99%
“…Although we have shown that the 3-carbon bridge can be used to conjugate PEG efficiently in aqueous solution 10,13 , insertion of the bridge also offers the potential to enable the site-specific conjugation of pharmacological and imaging agents to the protein [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%